"We're Constantly Learning": Identifying and Disrupting White Supremacy Within a Victim Services Organization. Issue 1 (January 2023) - Kulkarni, Shanti J.; Lawrence, Michelle; Roberts, Elizabeth
Many victim service organizations are seeking to realign service delivery around principles of racial equity. Dismantling institutional racism is a complex, intensive, and long-term process. Therefore, despite this imperative from the field, our knowledge about how social service organizations can effectively advance anti-oppressive practice is limited. This study examined victim advocate perspectives on the role institutional racism played within their work and the supports needed to undo institutional racism within their organization. Six focus groups were conducted with a meaningful cross section of staff members ( n = 53) across the organization. Semi-structured interview guides included questions in four domains: (1) racism within client work, (2) challenges to addressing racism, (3) effective solutions, and (4) helpful organizational supports. Transcripts were thematically analyzed using modified constructivist grounded theory methods. Two overarching themes, Identifying Institutional Racism in the Workplace and Advancing Anti-racist Practice, and six subthemes emerged from the analysis . Advocates identified that naming and becoming comfortable talking about race was essential. Further, they believed it was important to acknowledge the ways in which that racism was implicitly built into helping systems at large. Advocates explored how internalized racial stereotypes influenced interactions between black, indigenous, and people of color (BIPOC) and white advocates and their clients in complex ways. Advocates highlighted organizational efforts that supported ongoing personal reflection, the creation of an accountable community, and staff empowerment within the organization as being critical to advancing anti-racist practice. Some advocates also wanted to see the organization move further in the direction of standing with BIPOC communities, particularly around criminal justice concerns. Findings provide important timely insights into how institutional racism manifests within victim service organizations and what organizational actions encourage anti-oppressive practices and culture.